Are future medical oncologists sufficiently trained to communicate about palliative care? The medical oncology curriculum in Flanders, Belgium. Issue 5 (3rd September 2017) - Horlait, M.; Van Belle, S.; Leys, M.
Abstract : Background: Palliative care is considered an integral part of oncology and communicating this with patients is an unavoidable task for oncologists. This contribution investigated to what extent communication skills for communicating palliative care with patients are trained in the formal academic training program in medical oncology in Flanders, Belgium. The programme is based on the recommendations for a Global Core Curriculum in Medical Oncology, developed by The American Society of Clinical Oncology (ASCO) together with the European Society for Medical Oncology (ESMO). Methods: For this qualitative study, data were collected using document analysis from the ESMO/ASCO recommendations and the documents of the Flanders' medical oncology programme complemented with interviews with Flemish medical oncology trainees. Results: Few recommendations for training communication skills to communicate about palliative care were found in the ASMO/ASCO recommendations and even less in the Flanders' programme documents. Trainees are mainly exposed to palliative care communication during the clinical practice of their training. Only very few lectures or seminars are devoted to palliative care and even less on communication about palliative care. They reported several barriers to communicate about palliative care. Conclusions: This study revealed promising developments for the training of Flemish medical oncologists to discuss palliative care. However, there is still a need for more theoretical training on palliative care complemented with communication skills trainings. Communication training in general needs to be fully integrated as a core skill within the medical curriculum at large and should be promoted as lifelong learning and competency development.